Case-Based Learning for Creative Thinking Skills on the Ideal Gas Law: Application of the Understanding by Design Framework - Tutut Nurita; Lia Yuliati; Supriyono Koes Handayanto; Arif Hidayat; Phurkonni Saleah (Universitas Negeri Semarang, 2025)
The development of the 21st century and education are closely related in equipping students with relevant skills to adapt and succeed in an ever-changing environment. This development demands a more interactive, collaborative, and student-centered learning method. Case-based learning (CBL) is designed to facilitate students’ thinking critically and creatively in solving problems and working in teams so that they can face real-world problems that are integrated into learning. The Understanding by Design (UbD) framework facilitates cases in learning designed to suit students’ interests and needs, enhancing creative thinking skills when integrated with CBL. This study uses a mixed or explanatory method and involves 115 students. Quantitative data was obtained from creative thinking skills tests using pre-test and post-test, which showed differences between the pre-test and post-test and a correlation between creative thinking skills indicators (fluency, flexibility, originality, and elaboration). Qualitative data from classroom observations showed that students performed the activities well and were supported by interview data, which revealed that students were actively involved in learning, although some students could not relate concepts to problems. These findings support the idea that CBL with the UBD framework helps students understand the ideal gas law and improves creative thinking skills. This study suggests that students can develop better problem-solving skills because the UbD framework facilitates a structured and meaningful learning experience for students.